Identifikasi Preferensi Konsumen terhadap Desain Kemasan dan Kandungan Nutrisi Tepung Terigu di Daerah Istimewa Yogyakarta - Happy Suryaningsih; Didik Purwadi; Wahyu Supartomo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Consumer of wheat flour in Indonesia have at present more possibilities to choose the wheat flour because of more wheat flour products in market since governmental deregulation in October 1998. They choose the wheat flour based on their proposed final products and characteristics. Information's such nutritional facts, usage, expired date of wheat flour written in their packaging, but unfortunately those information does not depict the real condition. This can influence on the consumer preference. The research was conducted to identify the consumer's preferences on packaging design and nutritional fact in the wheat flour. Straified random sampling with the family welfare level based on BKKBN criteria was used in this research. Questionnaire was tested for validity and reliability by confidence level 95%, significance level 5 % and error sample 10 %. The result depicted that consumer index of packaging design for middle level 4.113 and 4.142 for high level respectively. The information of nutritional fact was ranked in second place for the second family welfare level. Based on the chi square test, the result depicted there were no differences among education level, age, sosial level and occupation to the consumer preferences on the nutritional facts. The result of t-paired test showed, there were significance differences on water and carbohydrate contents between the laboratory's determination and nutritional fact label. Meanwhile the ash and protein contents showed no differences.